2018
DOI: 10.1900/rds.2018.15.e1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Lung Disease: A Neglected Relationship

Abstract: BACKGROUND: Diabetes mellitus is a systemic disorder associated with inflammation and oxidative stress which may target many organs such as the kidney, retina, and the vascular system. The pathophysiology, mechanisms, and consequences of diabetes on these organs have been studied widely. However, no work has been done on the concept of the lung as a target organ for diabetes and its implications for lung diseases. AIM: In this review, we aimed to investigate the effects of diabetes and hypoglycemic agent on lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 130 publications
(166 reference statements)
0
9
0
Order By: Relevance
“…As periodontal diseases and lung cancer share many common and well-established risk factors, including smoking, alcohol use, and diabetes, 35,37,38 properly adjusted hazard ratios are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As periodontal diseases and lung cancer share many common and well-established risk factors, including smoking, alcohol use, and diabetes, 35,37,38 properly adjusted hazard ratios are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] In addition, insulin resistance and altered glucose homeostasis in patients with T2DM was associated with over-inflammation. [ 24 ] Thus, poor glycemic control worsens outcomes for patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Its airway hyperresponsiveness induces bronchoconstriction and chronic inflammation. 2 In one study, researchers identified 11 significant m 6 A regulators associated with asthma from the GSE40888 dataset. 46 Subsequently, five candidate m 6 A regulators were screened according to the nomogram model to predict the risk of childhood asthma.…”
Section: Role Of M 6 a Rna Methylation In Asthmamentioning
confidence: 99%
“…1 Lung diseases include asthma, chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), pulmonary hypertension (PH), and lung cancer. 2 COPD is a common chronic disease, which is the fourth leading cause of death in the world, with the characteristics of airflow obstruction. IPF is a kind of chronic progressive fibrosis interstitial pneumonia, which is characterized by dyspnea and gradual deterioration of lung function.…”
Section: Introductionmentioning
confidence: 99%